Physicochemical and functional characterization of flour from NSIC 2011 Rc 21 SR (Malagkit 5) and from two commercial waxy rice in the Philippines - Atencio, Sharmaine S.
Flours produced from two commercial waxy rice vended in a local market in Quezon City and from a newly developed Philippine-released waxy rice (NSIC 2011 Rc21 SR) were characterized in terms of proximate composition (moisture, protein, fat and total available carbohydrate) and physicochemical, functional, pasting, and thermal properties. The extent of rumbling in the commercial waxy rice was determined by visual inspection and found to be 8.8237 and 3.9600% for samples 1 and 2, respectively. Flours from commercial waxy rice samples had higher amylose content than that of their corresponding opaque grains, possibly due to the presence of non-waxy grains in the commercial waxy rice. Commercial waxy rice sample 1 had significantly higher (p<0.05) protein content, water and oil absorption capacities, and solubility, while its corresponding opaque grains had significantly higher (p<0.05) moisture content, bulk density, least gelation concentration and swelling power. Starch gelatinization occurred between 60.46 to 226.10OC. Flour from opaque grains of commercial waxy rice sample 2 had the highest peak gelatinization temperature. Values for pasting temperature and time, and peak, trough, final, and retrogradation viscosities were significantly highest (p<0.05) in the flour from commercial waxy rice sample 2. Panelists were unable to detect much difference between the kutsinta made from the flours of NSIC 2011 Rc21 SR, commercial waxy rice sample 1, and from its corresponding opaque grains. Variations may be due to amylopectin ratios, compositional, environmental, and varietal factors. Results may be useful in the development of novel waxy rice flour- based food products, and in promotion of cultivation of waxy rice varieties in the Philippines.